A study on the transmission of trade behavior of global nickel products from the perspective of the industrial chain. (March 2023) - Zhou, Xuanru; Zhang, Hua; Zheng, Shuxian; Xing, Wanli; Yang, Hanshi; Zhao, Yifan
Abstract: Critical Mineral is the important material basis for achieving carbon neutrality. Under a low-carbon scenario, the demand for nickel in the new energy will grow rapidly, which may lead to supply shortages. Under the Russia-Ukraine conflict, the nickel trade changes frequently and the trade will become more complicated. To clarify the risk transmission mechanism, based on the nickel products trade data of UN COMTRADE, this paper combines econometrics and complex network methods to construct the Global Nickel Industry Chain Trade Behavior Transmission Network (GNICTBTN). The research shows that the Main Transmission System of the GNICTBTN includes 18 countries and 25 trade links, of which 6 trade links need to be paid attention to in the middle and early stages of trade changes, and it indicates that nickel resource is at risk of being monopolized by middlemen. This study distinguishes the industrial chain structure of seven key countries, and finds that the relevance of trade links is closely related to trading transmission risk. According to GNICTBTN, we predict that the Russia-Ukraine conflict will affect the developing countries in the Asia-Pacific region and developed countries in Europe and USA in short term, and repeatedly affects the main transmission system for longer. Graphical abstract: Image 1 Highlights: Nickel trade transmission is mainly present in 25 trade links from 18 countries. Nickel resources may be monopolized by intermediate countries. The six critical countries have different trade transmission mechanisms. Six critical trade links need attention in the early middle stage of transmission. Ukraine will cause the greater impact of the nickel trade than Russia.